Experimentally validated study of the impact of operating strategies on power efficiency of a turbine array in a bi-directional tidal channel. (January 2021) - Hachmann, Christoph; Stallard, Tim; Stansby, Peter; Lin, Binliang
Abstract: Flexible operation across a wide range of operating conditions is required to maximise the contribution of tidal turbine arrays to the future energy mix. This study establishes a basin efficiency range of a small array of horizontal axis turbines between 0.45 and 0.79, with dependency on turbine operating point and flow direction. This range is largely due to variation of array thrust as array power varies by less than 15% for all operating points. Analysis of array thrust, power and wakes was conducted using a RANS actuator disc model and assessed against new experimental measurements using porous discs. RANS array thrust predictions are within 10% of the experimental study. Turbine thrust differs within each array, varying by −60% to +30% compared to isolated turbines. Row-specific operating points reduce this range by a factor of two whilst also increasing the basin efficiency slightly for a given flow speed. Accounting for time variation of basin efficiency reduces the energy yield by almost 5% relative to arrays modelled with a constant net array thrust coefficient. Arrays with row-specific local thrust coefficients generate similar net power to arrays with velocity-specific array operating points but reduce the occurrences of large rates of change of power. Highlights: Rated speed basin efficiency of a three-row tidal array ranges between 0.71 and 0.73. For operation below and above rated speed, basin efficiency ranges from 0.45 to 0.79. RANS-AD predicts net array thrust within 10% of experimental porous disc measurements. Variation of basin efficiency with flow speed can be specified to reduce power output variation. Corresponding average power output differs by up to 4.4% and onset velocity by 2%.